Prevalencia y factores de riesgo de la depresión en adolescentes - Gutiérrez Morocho, Lucila Anahí (2023)
Depression is a disease that alters a person's emotional state, and in adolescence, it is considered a priority attention problem due to its high prevalence, becoming the second leading cause of death worldwide; it is for all these reasons that this research work aims to establish the prevalence of the pathology and identify the most frequent risk factors of depression in adolescents in the American continent in the last ten years, and at the same time to describe the scientific evidence on this mental health problem, a non-experimental cross-sectional design was used, with a mixed descriptive and documentary approach based on bibliographic systematization. The study population was all that scientific evidence published in the databases Dialnet, Scielo, Science Direct, Redalyc and Elsevier during 2013-2023. Through the selection criteria, we delimited the sample to 32 scientific articles we obtained from which the following results: a high prevalence of depression in this age group belonging to the American continent, we identified being the female sex and among the associated risk factors personal, family, social and academic, having as most frequent low self-esteem, substance use, family dysfunctionality, violence, among others. To conclude, we evidenced the existence of scientific production on this mental illness, becoming an important precedent that allows health professionals to implement preventive strategies of primary and secondary care to their patients in the progression and maintenance of this pathology